Strategi Gamifikasi untuk Meningkatkan Kecakapan Bahasa Inggris di Sektor Outsourcing - Rojabi, Muhammad Afdan; Wang, Gunawan (Politeknik Harapan Bersama, 2024)
Foreign language proficiency, particularly in English, stands as a key factor in enhancing the competitiveness of the workforce. However, Indonesian workers are often found to lack fluency in English. Proficiency in the English language is considered a crucial element in preparing for Indonesia's golden era in 2045. The development of English language skills in Indonesia primarily does not occur within the school system but rather more extensively when entering the workforce. This report establishes a correlation highlighting the significance of English language mastery for the Indonesian workforce. The current decline in Indonesia's ranking can be addressed through the implementation of more effective learning methods. Gamification has proven to be a motivating tool for employees to actively participate in the learning process, thereby improving their English language skills and contributing to increased competitiveness. The Motivational Design ARCS (Attention, Relevance, Confidence, Satisfaction) model and the MDA (Mechanic, Dynamic, Aesthetic) framework are used as the basis for designing the gamification user interface in the process of enhancing English language skills. This approach aims to provide a gamification system that motivates employees to engage in language learning.Keywords – Gamification, English Language Proficiency, Outsourcing, ARCS Model, MDA Framework